Determinan Efisiensi Teknis Usahatani Tebu: Analisis DEA–Tobit di Kabupaten Kediri - Saputro, Arief Joko; Tebai, Natan; Yoga, Tirta (Jurnal Sosiologi Pertanian dan Agribisnis, 2026)
This study analyzes the technical efficiency of sugarcane farming in Kediri Regency by combining Data Envelopment Analysis (DEA) and Tobit regression to identify both efficiency levels and their determining socioeconomic factors. DEA results show that sugarcane farming in the region is generally not yet efficient, with an average technical efficiency score of 0.751 under the Constant Returns to Scale (CRS) assumption, 0.868 under Variable Returns to Scale (VRS), and a scale efficiency of 0.870. These values indicate considerable room for improving production performance, particularly through optimizing input use without reducing output. Tobit regression analysis further reveals that socioeconomic characteristics significantly influence the variation in technical efficiency. Three variables show a significant effect: ratoon frequency and farmer age negatively affect efficiency, while landownership status has a positive influence. Higher ratoon cycles reduce efficiency due to declining plant vigor and productivity, whereas older farmers tend to be less efficient due to physical limitations and slower technology adoption. In contrast, landowning farmers are more efficient because they possess stronger incentives and flexibility in farm management. Other variables and type, farming experience, family size, and formal education do not significantly affect efficiency. Overall, the findings highlight the need for improved ratoon management, increased engagement of younger farmers, strengthened land tenure security, and targeted technical training to enhance sugarcane farming performance in Kediri Regency. Government and